Historical And Ethnographic Analysis of Cultural Heritage Sites in the Kashkadarya Oasis - Rajabova, Nilufar (Indonesian Culture and Religion Issues, 2025)
This study presents a comprehensive and systematic documentation of cultural heritage sites located in the Kashkadarya Oasis, drawing on direct field observations and information obtained from local communities and oral testimonies. The research identifies and records a diverse network of architectural monuments, sacred structures, and pilgrimage sites that reflect the historical depth and cultural complexity of the region. Particular attention is given to the dynamic relationship between formally established Islamic architectural traditions and locally rooted, vernacular religious practices that continue to shape patterns of worship and community identity. The findings reveal that these heritage sites function not only as historical artifacts but also as living cultural spaces where religious, social, and historical meanings intersect. Consequently, the study emphasizes the urgent need for an integrated research framework that combines archaeological investigation with ethnographic approaches in order to ensure effective preservation, accurate interpretation, and sustainable management of the Kashkadarya Oasis as a significant cultural landscape.